Characterization and mechanical behaviour of similar and dissimilar parts joined by rotary friction welding - Houria, Benkherbache (Université de M'sila, 2020)
This work is a contribution to the study of the rigidity of rotational friction welding of cylindrical specimens made on a parallel lathe. We performed welding of three combinations of parts: steel / steel, aluminium / aluminium and steel / aluminium according to three numbers of rotations of the spindle (900, 1250 and 1800 rpm). To control the rigidity and quality of these assemblies, tensile tests are used followed by ultrasonic testing to ensure that the tips are welded and that there are no internal defects. Hardness profile of the welded zone according to the welding parameters was obtained. Metallographic observations have detected the profile of the various zones welded and affected thermally. The results of the mechanical tests showed that a rotation speed of 1250 rpm can produce a very good weld, with other parameters kept constant.
Keywords: Rotary friction welding Similar and dissimilar joints Integrity assessment